Inovasi Pembelajaran Flipped Classroom dalam upaya Penguatan Kompetensi dan Daya Saing Siswa Era Revolusi Industri 4.0 - Dedi Nurhadiat; Halimatus Syakdiyah (Peneliti.net, 2019)
Industrial era 4.0, is an era of challenges and hopes for the world of education. In this disruptive era the world of education must be able to tidy up and innovate in order to survive and continue to exist in the face of the challenges of the times. The World of Education has great hopes in the era of digitalization in an effort to achieve the achievement of educational goals. This article wants to provide an overview of the learning strategies of flipping class in 4.0 era with all its challenges. Based on the results of research that has been done proven effective calssroom flipping strategy can improve student chemistry learning outcomes. Then how should the learning strategy of flipping class be packaged in this disruptive era?